Research for Development : A World Bank Perspective on Future Directions for Research - Development Economics Senior Vice Presidency (2012)
This paper provides an overview of the history of development research at the World Bank and points to new future directions in both what we research and how we research. Six main messages emerge. First, research and data have long been essential elements of the Bank's country programs and its contributions to global public goods, and this will remain the case. Second, development thinking is in a state of flux and uncertainty; it is time to reconsider both the Bank's research priorities and how it does research. Third, a more open and strategic approach to research is needed -- an approach that is firmly grounded in the key knowledge gaps for development policy emerging from the experiences of developing countries, including the questions that policy makers in those countries ask. Fourth, four major sets of problems merit high priority for our future research: (i) securing economic transformation; (ii) broadening opportunities to participate in the benefits of, and contribute to, such transformation; (iii) dealing with emerging risks at all levels; and (iv) assessing the results of development efforts, including external assistance. Fifth, a new multi-polar world requires a new multi-polar approach to knowledge; the Bank must learn from, and collaborate with, developing-country researchers and institutes. Sixth, greater emphasis must be given to producing the data and analytic tools for others to do the research themselves and providing open access to those tools. And open data initiative needs to be extended to open knowledge. This will better inform development policy debates and allow for deeper engagement with the direct stakeholders in the outcomes of those debates.